2000
DOI: 10.1007/s001980070124
|View full text |Cite
|
Sign up to set email alerts
|

Bone Loss in Long-Term Survivors after Transplantation of Hematopoietic Stem Cells: A Prospective Study

Abstract: Organ transplantation is associated with relevant bone loss. Bone loss of up to 20% of pretransplant bone mineral density (BMD) values within the first year after kidney, liver, heart and lung transplantation has been reported. Patients undergoing transplantation of hematopoietic stem cells provide an interesting model to study transplantation-induced bone loss, especially because most patients do not have preexisting bone disease. A longitudinal study was performed in 81 patients undergoing bone marrow or per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
64
5
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 50 publications
(53 reference statements)
9
64
5
1
Order By: Relevance
“…The association between glucocorticoids and bone loss at various sites has been inconsistent in previous studies. [1][2][3][4][5] The lack of association with spine BMD loss in our study is unexpected as trabecular bone loss occurs most rapidly in glucocorticoid-induced osteoporosis. 8 At the more cortical site, the femoral neck, the lack of association suggests that cortical bone loss occurs by a distinct mechanism.…”
mentioning
confidence: 52%
See 3 more Smart Citations
“…The association between glucocorticoids and bone loss at various sites has been inconsistent in previous studies. [1][2][3][4][5] The lack of association with spine BMD loss in our study is unexpected as trabecular bone loss occurs most rapidly in glucocorticoid-induced osteoporosis. 8 At the more cortical site, the femoral neck, the lack of association suggests that cortical bone loss occurs by a distinct mechanism.…”
mentioning
confidence: 52%
“…2 Previous studies have shown that the most profound bone mineral density (BMD) decline occurs within the first 6 months following allo-SCT 3,4 but information regarding earlier change is limited. 2,3 Declines in BMD are greater at the femoral neck, a site rich in cortical bone, than lumbar spine, a site rich in trabecular bone, and this may suggest disproportionate cortical bone loss. 1,[3][4][5] This pattern is unlike the early spine BMD decline generally seen in postmenopausal and glucocorticoid-induced osteoporosis and suggests a unique mechanism.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Prospective studies have demonstrated that bone mineral density (BMD) is reduced in recipients of allogeneic haematopoietic stem cell transplants (alloSCT) (Stern et al, 1996;Ebeling et al, 1999;Kang et al, 2000;Schulte et al, 2000). This may increase the susceptibility to fragility fractures in these patients, although fracture data in this group of patients are limited.…”
mentioning
confidence: 99%